2015
DOI: 10.1519/jsc.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anthropometry, Upper-Body Strength, and Lower-Body Power Characteristics in Different Levels of Australian Football Players

Abstract: The aim of this study was to compare the anthropometry, upper-body strength, and lower-body power characteristics in elite junior, sub-elite senior, and elite senior Australian Football (AF) players. Nineteen experienced elite senior (≥4 years Australian Football League [AFL] experience), 27 inexperienced elite senior (<4 years AFL experience), 22 sub-elite senior, and 21 elite junior AF players were assessed for anthropometric profile (fat-free soft tissue mass [FFSTM], fat mass, and bone mineral content) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
5
35
1
Order By: Relevance
“…The remaining predictors occurring in the presented equations are consistent with reports of other researchers and include age [34], percentage of body fat [35], and length of body segments and indicators of its composition [2,33]. The research mentioned above indicate, among others, that there is a positive effect of age on the force-field capabilities in the 'squat' event, and on the sports result for bench press and squat in athletes with shorter legs.…”
Section: Discussionsupporting
confidence: 88%
“…The remaining predictors occurring in the presented equations are consistent with reports of other researchers and include age [34], percentage of body fat [35], and length of body segments and indicators of its composition [2,33]. The research mentioned above indicate, among others, that there is a positive effect of age on the force-field capabilities in the 'squat' event, and on the sports result for bench press and squat in athletes with shorter legs.…”
Section: Discussionsupporting
confidence: 88%
“…Significant FFMI differences were found between division levels, with higher values in Division I compared to Division II. Previous research has identified significant relationships between indices of body size, body composition, and physical performance outcomes relevant to football (3, 30, 33, 36). Differences in FFMI between divisions appear to mirror previously reported differences in physical performance outcomes between divisions (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional research has demonstrated that body composition differs among position groups (5, 7, 29, 32), and has identified a clear trend of increasing body size in recent decades (2, 16, 33, 35). American football requires a unique combination of speed, size, and power (12); as such, indices of body size and composition have been associated with strength (36), power (30), and career earnings (33) in football players, and extensive research in a variety of populations has documented relationships between various indices of fat-free mass (FFM) and strength, power, speed, and sport performance (1, 3, 24, 27, 28, 41, 43). However, absolute amounts of FFM are influenced by height, with greater height favoring higher FFM.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, increases in body mass or height are associated with greater career earnings in professional football players (29) and higher rating scores in high school recruits (10). Similarly, fat-free mass is correlated with various indices of strength, power, and competition level in Australian football players (4). Nearly all position groups prioritize the accretion of lean mass, based on the established links between lean body mass, strength, and power development (4, 27, 32).…”
Section: Introductionmentioning
confidence: 99%